The Effect of a Ferrocene Containing Camphor Sulfonamide DK-164 on Breast Cancer Cell Lines - Schröder, Maria; Yusein-Myashkova, Shazie; Petrova, Maria; Dobrikov, Georgi; Kamenova-Nacheva, Mariana; Todorova, Jordana; Pasheva, Evdokia; Ugrinova, Iva (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: Drug resistance is a major cause of cancer treatment failure. Most cancer therapies involve multiple agents, to overcome it. Compounds that exhibit strong anti-tumor effect without damaging normal cells are more and more in the focus of research. Chemotherapeutic drugs, combining different moieties and functional groups in one molecule, can modulate different regulatory pathways in the cell and thus reach the higher efficacy than the agents, which affect only one cellular process. Methods: We tested the effect of recently synthesized ferrocene-containing camphor sulfonamide DK-164 on two breast cancer and one breast non-cancer cell lines. The cytotoxic effects were evaluated using the standard MTT-dye reduction and clonogenic assays. The apoptotic or autophagic effects were evaluated by Annexin v binding or LC3 puncta formation assays, respectively. Cell cycle arrest was determined using flow cytometry. Western blot and immunofluorescent analyses were used to estimate the localization and cellular distribution of key regulatory factors NFΚB and p53. Results: Compound DK-164 has well pronounced cytotoxicity greater to cancer cells (MDA-MB-231 and MCF-7) compared to non-cancerous (MCF-10A). The IC50 value of the substance caused a cell cycle arrest in G1 phase and induced apoptosis up to 24 hours in both tumor cells, although being more pronounced in MCF-7, a functional p53 cell line. Treatment with IC50 concentration of the compound provoked autophagy in both tumor lines but is better pronounced in the more aggressive cancer line (MDA-MB-231). Conclusion: The tested compound DK-164 showed promising properties as a potential therapeutic agent.
Keywords: cell cycle arrest